To find the simplified equation corresponding to the measures of the angles, we know the following:
- Angle D E F is a right angle, so it measures 90 degrees.
- The angles D E G and G E F can be expressed in terms of \( x \):
- Angle D E G = \( 2x \) degrees
- Angle G E F = \( 5x - 22 \) degrees
Since angle D E F is composed of angles D E G and G E F, we can set up the equation:
\[ \text{Angle D E G} + \text{Angle G E F} = \text{Angle D E F} \]
Substituting the values we have:
\[ 2x + (5x - 22) = 90 \]
This simplifies to:
\[ 2x + 5x - 22 = 90 \]
Combining like terms gives:
\[ 7x - 22 = 90 \]
Now we rearrange it to match one of the given responses.
Thus, the correct equation based on our simplifications is:
(7x−22)°=90°.
So the answer is:
(7x−22)°=90°.